Analisis Kepatuhan Dan Efektivitas Pemungutan Pajak Bumi Dan Bangunan Dalam Meningkatkan Pendapatan Asli Daerah Di Kabupaten Pangkep - Wahyuni, Nur (Jurnal Online Manajemen ELPEI, 2024)
This study aims to determine and analyze the compliance and effectiveness of land and building tax (PBB) collection to increase local revenue in Pangkep Regency. Data collection methods are. used is documentation. interviews and observations. While the method of analysis in this study is a qualitative descriptive method. The results of the study show that the results of the analysis of compliance and the effectiveness of collecting land and building tax in Pangkep Regency with the observation period from 2017 to 2021 show that 2017 PBB compliance was 68.7% (quite compliant), 2018 namely 65.6% (moderately compliant), 2019 namely 67.2% (moderately compliant), 2020 namely 74.8% (moderately compliant) and 2021 namely 73.4% (moderately compliant). Whereas for PBB effectiveness in 2017 it was 84.84% (quite effective), 2018 it was 68.88% (less effective), 2019 it was 76.52% (less effective), 2020 it was 80.79% (quite effective), and 2021 of 46.98% (not effective). Obstacles experienced in collecting Land and Building Tax due to lack of awareness of taxpayers and less stringent sanctions that make taxpayers negligent in paying their taxes.